Implementation of STEM Integrated Ethnoscience-based Vocational Science Learning in Fostering Students' Higher Order Thinking Skills (HOTs) - PH, Qori Agussuryani; Sudarmin, Sudarmin; Sumarni, Woro; Subali, Bambang; Saptono, Sigit (International Journal of Active Learning, 2020)
The low HOTs of students is caused by the lack of opportunities to think scientifically. The research objective was to analyze HOTs profiles through Analyze (C4), Evaluate (C5), and Create (C6) indicators through science learning based on integrated ethnoscience STEM (Science, Technology, Engineering, and Mathematics). The research method was a quasi-experimental one-group pretest-posttest design with a purposive sampling technique in Class X SMK Accounting 1 which consisted of 37 students. The data collection method used HOTs test questions with the concept of "Waste and Its Handling". In-depth interviews were conducted to explore ethnoscience information in Wonosobo District. Documentation of the HOTs profile of SMK students and the surrounding environment in the Dieng Wonosobo plateau area. The t-test to analysis the effectiveness of STEM integrated ethnoscience learning in increasing HOTs. The results showed the HOTs profile of vocational students on the analyze indicator (C4) was 73.3%, evaluated (C5) was 71.5%, and created (C6) was 67.8%, Based on the t-test was tcount: 2.08, ttable: 2, 00, dk: 72, ÃŽÂ±: 5%, so tcount>ttable, then H0 rejected and H1 accepted means that there is the effectiveness of STEM integrated ethnoscience-based science learning in increasing the HOTs of SMK students. The contribution of exploring in ethnoscience information sources through STEM literacy